2021
DOI: 10.21203/rs.3.rs-766839/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contribution of IL-38 in Lung Immunity During Pseudomonas Aeruginosa-Induced Pneumonia

Abstract: Objective: Interleukin-38 (IL-38), a new type of cytokine, is involved in processes such as tissue repair, inflammatory response, and immune response. However, its function in pneumonia caused by Pseudomonas aeruginosa is still unclear.Methods: In this study, we detected circulating IL-38 in adults affected by pneumonia caused by P. aeruginosa. The P. aeruginosa-induced pneumonia WT murine model was adopted to evaluate the effect of IL-38 on Treg differentiation, cell apoptosis, survival, tissue damage, inflam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…As reviewed in this study, alterations in serum levels of IL-38 played a major role in the immunopathogenesis of many diseases, in which patients had been previously faced with a wide array of problems due to the lack of prognosis or accurate diagnosis and improper treatment [213][214][215][216][217][218][219][220][221]. At the time of the literature review for this systematic review study, as there is a global pandemic of Coronavirus, it has been demonstrated that anti-inflammatory properties of IL-38 can be considered as recently-emerged pharmacotherapies for alleviation of the inflammatory symptoms of patients with SARS-CoV-2 infection [186,222].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…As reviewed in this study, alterations in serum levels of IL-38 played a major role in the immunopathogenesis of many diseases, in which patients had been previously faced with a wide array of problems due to the lack of prognosis or accurate diagnosis and improper treatment [213][214][215][216][217][218][219][220][221]. At the time of the literature review for this systematic review study, as there is a global pandemic of Coronavirus, it has been demonstrated that anti-inflammatory properties of IL-38 can be considered as recently-emerged pharmacotherapies for alleviation of the inflammatory symptoms of patients with SARS-CoV-2 infection [186,222].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%